Space closure using aligners - Machado,Ricardo Martins (2020)
ABSTRACT Introduction: Due to the search for more aesthetic and comfortable alternatives to perform orthodontic treatments and to the great technological development, orthodontic aligners have assumed great importance. More and more complex treatments have been carried out with these appliances without, however, having all aspects involved in their use being studied in depth. Its biomechanical planning requires different approaches than those used in fixed orthodontics, as the force systems involved in movements, responses and side effects are distinct, and the professional must be prepared when opting for the technique. Objective: The objective of this article is to perform an evaluation of the force systems created on the space closure with aligners, its characteristics, and problems, as well as make some suggestions to overcome the difficulties inherent to its use. Conclusion: Space closure with aligners is possible, but depends on the correct selection of the patient, in addition to requiring the proper planning of the applied forces. The use of auxiliary resources and overcorrections to address the deficiencies of the aligner systems should always be considered. Digital planning should be used as a map of the force systems that will be applied, and not just as a marketing tool, keeping in mind that determining the objectives and the way to achieve them is the responsibility of the orthodontist, and that treatment plans must be individualized for each situation, following appropriate biomechanical precepts.